PENGARUH NILAI FRACTIONAL ANISOTROPY (DIFFUSION TENSOR IMAGING) PADA TERAPI IMPLANTASI KOKLEA DALAM KLINIS SENSORINEURAL HEARING LOSS (SNHL) - Purnawati, Heny; Amanda, Mega; Wulani, Vally; Serfina Fajarini, Eunike (JRI (Jurnal Radiografer Indonesia), 2020)
Background: Diffusion Tensor Imaging (DTI) on current MRI cochlear examination able to support the diagnosis and help determine implantation therapy. The DTI line can show the cochlea tract and fractional anisotropy (FA) values with reference to the control reference value. DTI can visualize white matter in the cochlear tract that can be mapped in the FA of the entire cochlear image using directions. The FA value on the MRI cochlear examination can be used to determine the continuation of implant placement in the patient by using the FA-DTI value in the case of sensorineural hearing loss (SNHL). Method: Data were taken from September 2018 to August 2019. The MRI sequences used were Axial T2 5mm, Coronal T2 2mm, Axial T2 2mm, Axial 3D Fiesta-C 0.4mm and DTI 2mm. The total time of examination was 20 minutes using post processing Functool on the 2mm DTI results, measuring the region of interest (ROI) to obtain FA values ​​in several segments, namely region Trapezoid Body (rTB), region Superior Olivary Nucleus (rSON), region Inferior Colliculus (rIC), region Medial Geniculate (rMG), region Auditory Radiation (rAR). Result:The results of the DTI image are very sensitive to produce a diagnosis in the form of nerve fibers. DTI which is supported by the results of the FA score is able to provide quantitative information. Conclusion: There is an effect on the FA-DTI value in SNHL cases for cochlear implant therapy.